Multiple drug resistance in bacterial isolates from liquid wastes generated in central hospitals of Nepal - Sharma, Dr; Pradhan, B; Mishra, SK (Kathmandu University Medical Journal, 2010)
Background: Healthcare liquid wastes are the reservoirs of harmful infectious agents such as the pathogens and multiple drug resistant microorganisms. Potential infectious risks include the spread of infectious diseases and microbial resistance from health-care establishments into the environment and thereby posing risks of getting infections and antibiotic resistance in the communities. Objectives: The objectives of this study were to assess the bacterial load of healthcare liquid waste generated in central hospitals and to explore the antimicrobial resistance pattern of these bacterial isolates. Materials and methods: A descriptive study was carried out in 10 conveniently selected central hospitals of Nepal during the period of May to December 2008. Effluent specimens from each hospital were subjected to total viable count studies by spread plate method in nutrient agar plate and incubated for 24 hours at 37°C using standard laboratory protocol. Similarly, all the specimens were cultured in Mac Conkey Agar media supplemented with 30 μg/ml of Chloramphenicol and 20 μg/ml of Gentamycin for the enumeration of multiple drug resistant (MDR) bacteria, which were further subjected to in-vitro antibiotic susceptibility test by modified Kirby Bauer disc diffusion technique for resistance patterns. Results: Total viable counts of hospital effluents significantly exceeded the standard heterotrophic plate count (p=0.000). Similarly, the numbers of multiple drug resistant bacteria were alarmingly high in three (more than 30% in 2 and 50% in 1) hospitals of this study. Drug resistant hospital effluent isolates showed simultaneous resistance for most of the antibiotics including Penicillin, Cephalosporin, Cotrimoxazole, Gentamycin and Quinolones. Conclusion: Healthcare liquid wastes were laden with MDR bacteria and seemed to pose a huge public health threat in the transfer of such resistance to the bacterial pathogens causing community acquired infections, thereby limiting our antibiotic pool. Key words: Healthcare liquid waste management; viable count; multiple drug resistance; hospitals; Nepal DOI: 10.3126/kumj.v8i1.3220 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 40-44